(untitled) (Fiep Bulletin - online, 2016)
This research has as the main goal identify and compare the maturity level of the fundamental movements and the level of body mass index and fat percentage of children aged 8 to 10 years of students from Rio de Janeiro. The sample consisted of 400 schoolchildren aged 8 to 10 years from ten public and private schools of Rio de Janeiro of both genders. The instruments used in the research were the Analysis Protocol of Fundamental Movements proposed by Gallahue e Ozmun (2005) that measures 23 movements organized in analysis classes to stability, locomotion and manipulative movements category; Body Mass Index Protocol proposed by OMS (2007) and Fat Percentage Classification Protocol proposed by Lohman (1997) - Triceps Skinfold and subscapular. The results revealed that children in general have shown in relation to the level of maturity of the basic fundamental movements. Considering the analysis with variation between initial, elementary and mature levels the data revealed fault in motor development as for this maturity. Children aged 10 years presented more mature level in relation to groups of children aged 8 and 9 years old. This result may be related to the time of motor task experienced by more mature children in relation to others. Regarding children aged 8 and 9 years old, the results show that they turned out to be very similar to each other with respect to the maturation of the fundamental movements Level. As for the Body Mass Index and Fat Percentage there was not much difference between the groups, most of the children had levels considered normal or near normal.